Utilizing host endogenous microRNAs to negatively regulate the replication of porcine reproductive and respiratory syndrome virus in MARC-145 cells. - Liwei Li; Fei Gao; Hao Zheng; Yifeng Jiang; Wu Tong; Yanjun Zhou; Guangzhi Tong (PLoS ONE)
MicroRNAs (miRNAs) contribute to gene regulation at the post-transcriptional level and are capable of mRNA silencing by binding to target sites exhibiting high degrees of complementarity. Therefore, cloning host miRNA-recognition sequences into the genome of RNA viruses represents a rational strategy for manipulating viral replication. Here, we performed deep sequencing to obtain small-RNA (sRNA)-expression profiles from in vitro-cultured MARC-145 cells post infection with porcine reproductive and respiratory syndrome virus (PRRSV) and chose six candidate miRNAs of different abundance (miR-21, miR-140-3p, miR-185, miR-26a, miR-505, and miR-199a) for further study. Based on the full-length cDNA clone p7USC, we constructed a number of PRRSV mutants that provided complementary base-pairing target sites for the miRNAs in 3' untranslated regions. Our results showed that all low- and moderate- abundant miRNA-target mutants showed similar growth properties, whereas the highest-abundant miRNA-target mutant blocked both viral transcription and replication. Discontinuous mutations in high-abundant miRNA-target sites subsequently recovered viral viability and propagation. These results demonstrated the copy number of endogenous miRNAs and the extent of sRNA complementarity were key factors to silence potential mRNA expression/translation, thereby determining PRRSV viability. Interestingly, the mutant containing miR-140-target sites (v140-t) showed strong suppression of viral replication from P1 to P3 in vitro, as shown by virus titer, plaque morphology, and qRT-PCR assays. To assess genetic stability, sequencing of v140-t (P1, P3, P5 and P10) revealed spontaneous mutations preferentially located among several nucleotides near the 3' end of the insertion region and corresponding to the "seed region" of miR-140-3p, explaining the induced viral repression and the direction of virus evolution. This approach provided a general silencing strategy for limiting PRRSV replication by endogenous miRNAs in MARC-145 cells.